Resetting the Hsc70-mediated lysosomal degradation of PD-L1 via a supramolecular meso peptide for the restoration of acquired anti-tumor T cell immunity - Yujia Zhao; Dan Liu; Wenguang Yang; Wangxiao He; Jin Yan; Leiqing Yao (Journal of Nanobiotechnology)
Abstract The reduction of cellular PD-L1 abundance through lysosomal degradation is recognized as essential for effective and sustained targeting of PD-L1-dependent immune evasion in cancer. While Hsc70 can interact with PD-L1 to promote its lysosomal degradation, the overexpression of CMTM6 competitively inhibits this interaction, leading to the blockade of PD-L1 lysosomal degradation. To overcome this issue, a meso chimeric peptide PEPPDL1 was designed to specifically bind the PD-1 binding domain of PD-L1 instead of the Hsc70/CMTM6 binding domain, while also binding to Hsc70 to facilitate the dragging of PD-L1 into Hsc70-mediated chaperone-mediated autophagy (CMA), thereby achieving lysosomal degradation. In order to enable internalization into tumor cells, supramolecular engineering techniques were employed through terminal modification involving sulfydryl and monovalent gold ion (Au(I)), both facilitating self-assembly of modified PEPPDL1 into supramolecular nanospheres termed CTAC-PDL1 driven by aurophilic interaction. Furthermore, based on bioinformatics analysis of mRNA expression data from 30 types of tumors obtained from TCGA database, malignant melanoma was identified as the most suitable indication for CTAC-PDL1 due to its specific characteristics of tumor immune. As expected, CTAC-PDL1 effectively reactivated Hsc70-mediated lysosomal degradation of PD-L1 and consequently restored anti-tumor T cell immunity in a B16F10-derived mouse model of malignant melanoma while maintaining a favorable safety profile. Overall, this work not only presents an alternative approach for targeting PD-L1-dependent cancer immune evasion, but also provides a modularized strategy for discovering specific regulators for target proteins in various diseases.